The Relationship Between Spousal Support And Psychological Well-Being In Hiv Aids Patients Who Are Housewives In Hospital Sultan Imanuddin Pangkalan Bun - Aini Zulaiha, Nurul; Zuliya Indah Fatmawati; Wahyono (Infomasi dan Promosi Kesehatan, 2025)
Introduction: HIV AIDS is a disease that attacks the immune system, makes patients vulnerable to opportunistic infections and other health complications. Globally, in 2023, there were be 39.9 million people living with HIV and 1.3 million new HIV infections. In Asia and the Pacific, new HIV infections are increasing, where they have been declining for 10 years. HIV AIDS patients tend to experience various physical, psychological, and social stresses. This affects the psychological well-being of sufferers so that people with HIV AIDS (PLWHA) need social support. One of the social supports needed is support from a partner; this support increases the positive mood and psychological well-being of sufferers. Methods: This study a descriptive correlational design and a cross-sectional approach with a sample of 36 respondents. The sampling technique used was purposive sampling. Data collection used the social support scale (SSS) instruments and Ryff's Psychological Well-Being Scale. Univariate data analysis of this study with frequency distribution, while bivariate analysis used the Spearman Rank test. Results: All respondents received good spousal support. Most had very high psychological well-being, and almost half were in the high category. Spearman test results showed (p = 0.667 > 0.05). It means that H0, that is, there is no relationship between spousal support and psychological well-being at Sultan Imanuddin Pangkalan Bun Hospital. Conclusion: This study shows that high spousal support does not correlate with the psychological well-being of HIV AIDS patients who are housewives at Sultan Imanuddin Pangkalan Bun Hospital.